Political initiation in the novels of Philip Roth - Brühwiler, Claudia Franziska (Bloomsbury Academic, 2013)
Political Initiation in the Novels of Philip Roth exemplifies how literature and, specifically, the work of Philip Roth can help readers understand the ways in which individuals develop their political identity, learn to comprehend political ideas, and define their role in society. Combining political science, literary theory, and anthropology, the book describes an individual's political coming of age as a political initiation story, which is crafted as much by the individual himself as by the circumstances influencing him, such as political events or the political attitude of the parents. Ph.